Felipe Padilla de Leon memories of my father : an interview with Felipe de Leon, Jr - Mirano, Elena Rivera (Musika Jornal, 2014)
Felipe Padilla de Leon was arguably the most politically involved composer of the 20th century. This interview with the composer's eldest son and close associate, Felipe de Leon, Jr., Professor of Humanities and Art Studies and now head of the National Commission for culture and the Arts, gives us intimate insights into the personal history of the composer, the world that he lived in, the major influences on his life and work, and his perception of his role in the shaping of the world he inhabited.